Pengaruh Remedial Dan Lingkungan Sosial Terhadap Kesulitan Belajar Peserta Didik Di Sekolah - Nelly Agustina; A. Amiruddin Tawe; Haedar Akib (Phinisi Integration Review, 2022)
Education is one of the essential things in life. The ability of each student in understanding the material being taught varies, some are fast, moderate, slow, and even difficult. Students who experience difficulty in understanding the material will be incomplete in their learning results. The rights of students to get the same knowledge as others, students who are declared incomplete are given remedial. One of the obstacles for students in achieving success in learning is students have learning difficulties. Learning difficulties are conditions where students with average or above-average intelligence abilities have learning disabilities or failures related to obstacles in the process of perception, conceptualization, language, memory, as well as concentration, self-control, and motor sensor integration function. Therefore, this study aims to discover 1) the influence of remedial on students’ learning difficulties at SMAN 9 Makassar, 2) the influence of social environment on students’ learning difficulties at SMAN 9 Makassar, and 3) the influence of remedial and social environment on students’ learning difficulties at SMAN 9 Makassar. The type of this study is survey research with a quantitative approach. The results of the study indicate that there is a remedial influence on learning difficulties. The test results show that 1) there is a positive and significant remedial influence on students' learning difficulties through remedial learning, 2) there is a positive and significant social environment influence on students' learning difficulties through motivation from the surrounding environment, and 3) there is a positive and significant remedial and social environment on students’ learning difficulties both partially and simultaneously.